Study of microbial communities of uranium deposits (Eurasian Journal of Ecology, 2016)
The paper considers problems in studies of microbial cenosis uranium deposits of “Kanžugan” and “Uvanas” which is the suzak district of the South Kazakhstan region. The results of the research were made the representatives of hemolitotrofnyh bacteria A. ferrooxidans and A. thiooxidans. The presence of these bacteria in the acid leaching solution indicates that the oxidation process of uranium-bearing ore is between these cultures.
Keywords: microorganism; microbocenos; hemolitautotrophic bacteria